Efficacy of wild basidiomycetes as new biocontrol agents against Curvularia leaf spot disease on oil palm / Mohd Ramdzan Md Jadi - Md Jadi, Mohd Ramdzan (Faculty of Plantation and Agrotechnology, 2018)
Malaysia is among the top countries in the world as oil palm producer. nowadays, the value of oil palm production plays a significant role in Malaysia economic growth. the widespread of curvularia leaf spot disease that caused by curvularia sp. has become the major problem because the disease hard to be eradicated and taken several methods to eliminate it. therefore, the main objectives of this study were to screen and evaluate the effectiveness of wild basidiomycetes in vitro and in vivo ways which suspected have antagonistic activity against curvularia leaf spot disease on oil palm seedlings. next to determine the most effective wild basidiomycete isolate against curvularia leaf spot disease causal agent. in this study, five species of wild basidiomycete isolates named CS1, CS2, CPP2, CJBBB and cbc were selected to determine its antagonistic activities against curvularia leaf spot disease on pda. in vitro studies, the causal agent of curvularia leaf spot and wild basidiomycete isolates were grown on a PDA in dual culture assays. the highest percentages of mycelial inhibition growth rate for wild basidiomycete isolates named CPP2 and CS1 were about 38.67% and 22.64%, respectively. in vivo studies, the effectiveness of wild basidiomycetes culture filtrates named CS1 and CPP2 have been evaluated by sprayed on oil palm leaves which artificially infected by curvularia leaf spot disease in green house. the data retrieved from in vitro and in vivo studies were analyzed by using one way anova in minitab software. the obtained results have shown that wild basidiomycete isolate named CPP2 has the highest inhibition rate were about 0.22 cm on curvularia leaf spot disease symptom development on oil palm leaves compared with others tested wild basidiomycete isolates.